Understanding the Correlation Between Visual Impairment and Mental Health: A Literature Review - Avizena Muhammad Zamzam (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Low vision is one of the major ophthalmologic problems and the leading causes of disability in older adults associated with reduced quality of life and increased depressive symptoms. In turn, depression may cause a further decline in quality of life, may aggravate disability caused by the visual impairment, and may increase vulnerability for health decline. Approximately around 36 million are blind, and 217 million have marked moderate to severe visual impairment. Visual impairment refers, generally, to poor vision. Observational data revealed that those with sight loss were twice as likely as those with another impairment to have experienced discrimination. There is evidence that individuals with visual impairment have poorer mental health than their impairment-free counterparts. In health care settings, an association between visual impairment and depression has been consistently reported. Greater prevalence of depressive symptoms in those with visual impairment has also been reported. The aim of this review is therefore to summarize the literature with the goal to untangle the relationship between vision loss and psychological factors that lead to mental health disturbance.